2022
DOI: 10.1080/20008066.2022.2114260
|View full text |Cite
|
Sign up to set email alerts
|

Comparing PTSD symptom networks in type I vs. type II trauma survivors

Abstract: Background: Network analysis has gained increasing attention as a new framework to study complex associations between symptoms of post-traumatic stress disorder (PTSD). A number of studies have been published to investigate symptom networks on different sets of symptoms in different populations, and the findings have been inconsistent. Objective: We aimed to extend previous research by testing whether differences in PTSD symptom networks can be found in survivors of type I (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Fourth, we tested a heterogenous sample of trauma survivors with PTSD. However, there is a first indication from a cross-sectional network study that trauma type may be a moderator (Stefanovic et al, 2022 ). Therefore, future studies should include other variables such as frequent comorbid symptoms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we tested a heterogenous sample of trauma survivors with PTSD. However, there is a first indication from a cross-sectional network study that trauma type may be a moderator (Stefanovic et al, 2022 ). Therefore, future studies should include other variables such as frequent comorbid symptoms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic stress studies have separately considered the single-incident traumatic event (e.g., traffic accident) known as type I trauma and persistent trauma exposures (e.g., interpersonal conflicts), also known as type II trauma 23 . And, they also have suggested that type II trauma exposures might have stronger associations with PTSS severity than type I traumatic experiences 24 . Our respondents have reported prolonged suffering owing to the disaster.…”
Section: Discussionmentioning
confidence: 99%
“…The use of network analysis, a relatively new tool in this field of study, appears promising. Stefanovic et al (2022) identified significant differences in PTSD-symptom networks in survivors of type I trauma (single event; sudden and unexpected high-level threat), as against type II (repeated and/or protracted; anticipated) trauma. Given the close relationship between PTSD and moral injury, such analysis may see new patterns of correlation identified between trauma types and symptom networks of moral injury among HCWs, beyond a generalized list of guilty feelings, shame, powerlessness, and anger.…”
Section: Divergent Experiencesmentioning
confidence: 94%